Fronteiras da sanidade: ‘Periculosidade' e ‘risco' na articulação dos discursos psiquiátrico forense e jurídico no Instituto Psiquiátrico Forense Maurício Cardoso de 1925 a 2003 - Almeida, Francis Moraes de (2013)
Este artigo analisa a articulação entre os discursos jurídico e psiquiátrico forense nos laudos do Instituto Psiquiátrico Forense Maurício Cardoso entre 1925 e 2003. Adotando uma abordagem arqueogenealógica inspirada em Michel Foucault, descreve os regimes de verdade jurídico-legais e médico-científicos em que emergem as noções de periculosidade e risco. Até 1973, há o predomínio da periculosidade, segundo a qual determinantes hereditários e de personalidade tendiam a ser associados ao comportamento criminoso violento. A partir daí, emerge a noção de risco, centrada na determinação de potenciais reincidências com ênfase na classificação psiquiátrica. The article Borders of Sanity: The ‘Dangerousness' and ‘Risk' In Synthesising the Forensic Psychiatric and LeÂgal Lines of Discourse at the Maurício Cardoso Forensic Psychiatric Institute From 1925 To 2003 analyses the way the legal and forensic psychiatric arguments were engaged in the reports of the Maurício Cardoso Forensic Psychiatric InstiÂtutions from 1925 to 2003. Adopting an archeogeneological approach drawn from Michel Foucault, it describes the legal and medical-scientific regimes of truth in which the notions of dangerousness and risk emerge. Until 1973, the notion of dangerousness was dominant, according to which herediÂtary and personality determinants tended to be associated to violent criminal behavior. Since then, the notion of risk has emerged, centered on the determination of potential recurÂrences with emphasis on psychiatric classification. Keywords: crime, insanity, dangerousness, risk, Maurício Cardoso Forensic Psychiatric Institute